2008
DOI: 10.3748/wjg.14.6975
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of Fitz-Hugh-Curtis syndrome mimicking acute biliary disease

Abstract: AIM:To analyze the clinical characteristics of patients diagnosed with Fitz-Hugh-Curtis syndrome. METHODS:The clinical courses of patients that visited St. Mary's Hospital with abdominal pain from January 2005 to December 2006 and were diagnosed with Fitz-Hugh-Curtis syndrome were examined. RESULTS: Fitz-Hugh-Curtis syndrome was identified in 22 female patients of childbearing age; their mean age was 31.0 ± 8.1 years. Fourteen of these cases presented with pain in the upper right abdomen alone or together with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 17 publications
1
42
0
1
Order By: Relevance
“…The diagnostic standard was abdominal CT scan that showed pelvic inflammation with contrast enhancement of hepatic capsules and adhesions between the liver and the diaphragm or the liver and the abdominal wall detected by laparoscopy. Twenty out of 22 patients visited the emergency room due to acute abdominal pain, 32% of which was spotted in the right upper abdomen, 32% both in the right upper abdomen and in the lower abdomen, 27% only in the lower abdomen, while 4.5% presented with fever and 4.5% with epigastric pain [11].…”
Section: Methods and Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnostic standard was abdominal CT scan that showed pelvic inflammation with contrast enhancement of hepatic capsules and adhesions between the liver and the diaphragm or the liver and the abdominal wall detected by laparoscopy. Twenty out of 22 patients visited the emergency room due to acute abdominal pain, 32% of which was spotted in the right upper abdomen, 32% both in the right upper abdomen and in the lower abdomen, 27% only in the lower abdomen, while 4.5% presented with fever and 4.5% with epigastric pain [11].…”
Section: Methods and Findingsmentioning
confidence: 99%
“…Fitz-Hugh-Curtis syndrome is more common in women of reproductive age who visit hospitals due to acute pain and tenderness in the right upper abdomen [11]. This pain is caused by adhesion of the anterior hepatic surface and the abdominal wall [12].…”
Section: Introductionmentioning
confidence: 99%
“…Woo et al [1] in 2008 reported one out of the 22 female FHCS patients to be positive for U. urealyticum. So far, our patient is the second incidence worldwide to associate U. urealyticum with FHCS.…”
mentioning
confidence: 98%
“…Up to date, FHCS is mainly attributed to Neisseria gonorrhoeae and Chlamydia trachomatis infection while the role of other microorganisms is yet unknown [1]. Definite diagnosis of FHCS is made by assessment of perihepatic adhesions via diagnostic laparoscopy and both conventional microbiological methods and nucleic acid amplification techniques are used to isolate the responsible organism [2].…”
mentioning
confidence: 99%
“…The FHC syndrome typically presents without or only faint involvement of the liver parenchyma. While Neisseria gonorrhoeae was the first established pathogen [1,2], Chlamydia trachomatis is incriminated in most cases nowadays [3]. The pathophysiology of perihepatitis FHC is unclear, but direct infection of the liver capsule, hematologic or lymphatic spread as well as an exaggerated immune response have been suggested [4].…”
mentioning
confidence: 99%